The Effect of Brand Image and Product Quality on Purchasing Decisions of Sajang Kopina - Parman Wira Yuda; Dwi Putra Buana Sakti; Akhmad Sufi (Tinta Emas Institute, 2023)
This study aims to determine the effect of brand image and product quality on purchasing decisions for Kopina Sajang. This type of research is quantitative research with a casual associative approach. The sample used in this study was 100 people. The data collection method used is a survey sample. the measurement scale uses a Likert scale measurement scale. The analytical tool used is multiple linear regression which is analysed using SPSS 20 For Windows. The results showed that there was a positive and significant influence between brand image and purchasing decisions for Kopina Sajang. There is a positive and significant influence between product quality and purchasing decisions for Kopina Sajang. This means that the higher the brand image and product quality, the more purchasing decisions for sajang coffee will increase.